Teaching principles for the development of the quality monitoring system for prospective masters in stomatology in the educational environment of the university - Maryna Grynova; Nataliia Dorokhova; Valeriy Zhamardiy; Olena Shkola (Política e Gestão Educacional, 2022)
The need for qualitative assessment of prospective Masters in Stomatology professional competence requires continuous monitoring of the educational process to find ways to improve it in all components. The study empirically tests the didactic principles of monitoring the quality of education of prospective Masters in Stomatology in the university's educational environment. The research was conducted at Poltava State Medical University in five stages during 2019–2022. The study utilizes the methods of theoretical, empirical questionnaires, surveys, pedagogical testing, and observation. Given the results, the didactic principles (the scientific principle, accessibility, systematization and coherence, visibility, control and correction of knowledge, strength of knowledge, connection between theory and practice, optimization of learning) in the general didactic context are designed to regulate the learning process, control over it and evaluation of program learning results, and act as a methodological basis for monitoring the quality of education of prospective Masters in Stomatology in a medical institution of higher education.